Vrednote, ekonomska rast in družbeni razvoj - Hafner-Fink, Mitja (Teorija in praksa, 2016)
The article is based on various debates on the role of values in social development and how to leave behind approaches that reduce development to economic growth. An empirical test is shown of "a development" model of relations among the following four aspects of development: economy, culture and values, democracy, and quality of life. The model's conceptual framework builds on elements of modernisation theory (according to Inglehart). Data from the European Values Study and World Values Survey were used to test the model. The analysis shows that the values of self-expression, together with the system's integrity, are important factors supporting development in the direction of quality of life. Observing changes in Slovenia in the period from its independence until 2011 support the thesis about the impact of values and the relationship between values and economic development - the decrease in self-expression values took place even before the economic crisis started.
Keywords: Družbeni razvoj; Economic growth; Ekonomska rast; Javno mnenje; kvaliteta življenja; Public opinion; Slovenia; Slovenija; Social evolution; Values; Vrednote